2010
DOI: 10.1071/py10027
|View full text |Cite
|
Sign up to set email alerts
|

Utilising implementation science in building research and evaluation capacity in community health

Abstract: It is becoming increasingly important for the community health sector to provide evidence of practice and program effectiveness. Unfortunately many community health centres do not have the capacity to provide such evidence and require the implementation of innovative changes within their organisation to develop their capacity to conduct research and evaluation. In this paper we present our project in which we utilised Donald Ely's model to build research and evaluation capacity in a community health centre. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 14 publications
1
23
0
Order By: Relevance
“…A range of strategies are required that include motivators and enablers and also measures to reduce the barriers to research. Several studies in the literature have reported success with RCB strategies that use multistrategy, multilevel coordinated approaches 13,21,42. Results of this study add to this literature by suggesting that strategies that target those AHPs who express an intention to do research may be more efficient and effective than strategies that target the entire workforce.…”
Section: Discussionsupporting
confidence: 52%
“…A range of strategies are required that include motivators and enablers and also measures to reduce the barriers to research. Several studies in the literature have reported success with RCB strategies that use multistrategy, multilevel coordinated approaches 13,21,42. Results of this study add to this literature by suggesting that strategies that target those AHPs who express an intention to do research may be more efficient and effective than strategies that target the entire workforce.…”
Section: Discussionsupporting
confidence: 52%
“…A total of 8492 unique records were assessed for eligibility by screening titles and abstracts. Of these, 20 were reviewed in full-text and six were included in the review [ 9 , 29 , 33 , 37 , 40 , 41 ]. Figure 1 illustrates the number of studies which were screened based on title/abstract and full-text, with reasons for exclusion documented.…”
Section: Resultsmentioning
confidence: 99%
“…Eight papers [ 11 , 24 30 ] were rated strong and 11 papers were rated moderate [ 31 41 ]. Most of the moderate ratings were due to theories, models or frameworks being implied versus explicitly stated.…”
Section: Resultsmentioning
confidence: 99%